Influence of genetic polymorphism on sports talent performance versus non-athletes: a systematic review and meta-analysis - Cirley Pinheiro Ferreira; Valmir Oliveira Silvino; Rebeca Gonçalves Trevisano; Rayane Carvalho de Moura; Sandro Soares Almeida; Marcos Antonio Pereira dos Santos (BMC, 2024)
Abstract Background Talented athletes exhibit remarkable skills and performance in their respective sports, setting them apart from their peers. It has been observed that genetic polymorphisms can influence variations in sports performance, leading to numerous studies aimed at validating genetic markers for identifying sports talents. This study aims to evaluate the potential contribution of genetic factors associated with athletic performance predisposition in identifying sports talents. Methods A systematic review was conducted following the PRISMA framework, utilizing the PICO methodology to develop the research question. The search was limited to case-control studies published between 2003 and June 2024, and databases such as Medline, LILACS, WPRIM, IBECS, CUMED, VETINDEX, Web of Science, Science Direct, Scopus and Scielo were utilized. The STREGA tool was employed to assess the quality of the selected studies. Results A total of 1,132 articles were initially identified, of which 119 studies were included in the review. Within these studies, 50 genes and 94 polymorphisms were identified, showing associations with sports talent characteristics such as endurance, strength, power, and speed. The most frequently mentioned genes were ACTN3 (27.0%) and ACE (11.3%). Conclusion The ACE I/D and ACTN3 R577X polymorphisms are frequently discussed in the literature. Although athletic performance may be influenced by different genetic polymorphisms, limitations exist in associating them with athletic performance across certain genotypes and phenotypes. Future research is suggested to investigate the influence of polymorphisms in elite athletes from diverse backgrounds and sports disciplines.